Financing of the Icelandic Airports based on the Norwegian system - Sigríður Alma Gunnsteinsdóttir 1986- (2016)
In the current airport system in Iceland the domestic airports and Keflavík International Airport are financed separately and with a separate scheme of charges. In this study a decision support system (DSS) was developed to model the current financing of the airport system and to show how the system could be financed, based on the Norwegian one. The model evaluates the financial condition of the network as a whole, including all airports in Iceland that Isavia operates. The principle of the new system is that all airports have their own financial outcome, where the profit from the profitable airports is used to cover the losses from the unprofitable ones, and the airport system is operated without external aid from the state. The result of the study showed how predicted number of passengers could affect the financial outcome for the next ten years, both for the current system and the new one. Due to large investment projects at Keflavík Airport for the upcoming years, the profit from that airport is very important for the operation and investments. Nevertheless Isavia should consider adjusting the operation to the Norwegian model. It would be preferable for Isavia if the system could be financed from within, with no external aid from the state. If the financing would be based on the Norwegian system, the operation of the Icelandic airports would be profitable in the long term according to the assumptions made. This study was supported by a grant from Isavia. Keywords: Decision support system (DSS), Prediction, Financing, Operation of airports. Innanlandsflugvellir á Íslandi og alþjóðaflugvöllurinn í Keflavík eru reknir og fjármagnaðir í sitthvoru lagi í dag og er notast við sitthvora gjaldskránna. Í verkefninu var búið til ákvarðanatökulíkan sem var notað til þess að bera saman núverandi afkomu flugvallanna og mögulega afkomu ef kerfið væri rekið að norskri fyrirmynd. Líkanið metur fjárhagsstöðu á öllum flugvöllum sem Isavia rekur, og var niðurstaða heildarnetsins skoðuð. Grunnhugmyndin í nýja kerfinu er að ...